The environmental kuznets curve in the CEE countries- the threshold cointegration approach - Piłatowska, Mariola; Włodarczyk, Aneta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the paper is the investigation of the long-run relationship between carbon dioxide emissions and economic growth in the Central and East European countries with special emphasis on a decoupling of carbon emissions and economic growth. The implementation of threshold cointegration with asymmetric adjustment enables detecting the changes in the non-linear pollutant-income relationship in the long-run, and in consequence allows to identify the non-linear causal link among CO2 emissions, GDP and energy consumption in a more comprehensive way and formulate more reliable recommendations for energy policy. The main contribution of the paper lies in testing the standard EKC hypothesis and its extended version by adding energy consumption and time trend for the CEE countries in order to test the robustness of the results. We also concentrate on the identification of the short-run and long-run causal relationship between per capita CO2 emissions and per capita income using threshold error correction models (T-ECM) and momentum threshold error correction model (M-TECM). There is significant evidence that the inverted U-shape (EKC) holds between per capita CO2 and GDP per capita for the Czech Republic, Slovakia and Romania meaning that economic growth decouples from CO2 emissions. This finding can be interpreted in terms of effective environmental policy directed into the reduction of CO2 emissions in these countries. We also find that temporary disequilibrium from the long-run EKC is corrected in an asymmetric fashion for Romania, Slovenia, Estonia in the framework of the standard EKC model, and additionally for the Czech Republic and Bulgaria (besides Slovenia and Estonia) based on the extended specification of EKC model
Argumenta Oeconomica, 2017, Nr 2 (39), s. 307-340
Keywords: Environmental Kuznets curve; decoupling economic growth from carbon dioxide emissions; energy consumption; threshold cointegration; nonlinear error correction